The NBA Isn't What It Used to Be: Racialized Nostalgia for '90s Basketball. Issue 2 (20th December 2021) - Karakaya, Yagmur; Manning, Alex
Abstract : Soon after the Covid19 pandemic hit, sports were halted, resulting in a natural hiatus ripe for collective memory practices. For basketball culture, this remembrance predominantly took the form of nostalgia, mostly for the 1990s and the Michael Jordan era through ESPN's series The Last Dance; when professional men's basketball is considered to have been better. In this paper, we ask what this perceptional superiority signifies. We find that the nostalgic story of '90s NBA, told by fans and media pundits, has three characteristics. First, the game was tougher, competitive, not amicable, less globalized, hence, more masculine. Second, team loyalty mattered more in the past and hence players stayed with a sole team, as they tried to defeat worthy rivals. Third, the sport was apolitical. We argue that this sporting nostalgia, which intersects with dominant ideas about masculinity, competition, celebrity, and American society's "apolitical" relationship to sport, is used as a cultural corrective to police the actions of current Black NBA players on and off the court. Through the juxtaposition of lead characters of Michael Jordan and Lebron James, nostalgia is used as a racialized symbolic boundary marker to reinforce and produce the "right" professional Black athlete deserving of public adoration.